Pengelolaan Pembelajaran Soft Skill di UPT BLK Kabupaten Rembang - Inggil Wijayatika; Abdul Malik (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
The purpose of this study is to analyze the process of managing soft skills learning at UPT BLK Rembang Regency, and to describe the results of soft skills learning management at UPT BLK Rembang Regency. This study uses a qualitative method. The technique of checking the validity of the data is using source triangulation. Data analysis techniques in this study used data reduction, data presentation, and drawing conclusions. The results of research on the management of soft skills learning at UPT BLK Rembang Regency include the process of managing soft skills learning and the results of managing soft skills learning at UPT BLK Rembang Regency. There are three stages in the learning management process, namely: 1) Planning, 2) Implementation, and 3) Evaluation. The results of the management of soft skills learning can support the skills of students from the results of computer vocational training learning with soft skills learning which is a separate added point in improving students' skills for use in the world of work. The future sustainability of the results of the management of soft skills learning can minimize unemployment and open new jobs that have a big impact on the world of work. The existence of soft skills learning can support the learning outcomes of computer materials that affect the knowledge of students' skills. The holding of soft skills learning to increase work productivity as a supporter of competency test certificates owned by graduates.